2007
DOI: 10.1021/la702741q
|View full text |Cite
|
Sign up to set email alerts
|

Salt Effect on the Heat-Induced Association Behavior of Gold Nanoparticles Coated with Poly(N-isopropylacrylamide) Prepared via Reversible Addition−Fragmentation Chain Transfer (RAFT) Radical Polymerization

Abstract: Poly(N-isopropylacrylamide) (PNIPAM) with a narrow molecular weight distribution was prepared by reversible addition-fragmentation chain transfer (RAFT) radical polymerization. A dithioester group at the chain end of PNIPAM thus prepared was cleaved by treating with 2-ethanolamine to provide thiol-terminated PNIPAM with which gold nanoparticles were coated via reactions of the terminal thiol with gold. The thermoresponsive nature of the maximum wavelength of the surface plasmon band and hydrodynamic radius (Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 32 publications
(46 reference statements)
7
93
0
Order By: Relevance
“…1b, it is clear that the absorption spectrum of IDA-Ag NPs underwent a little red-shift compared with that of bare Ag NPs, which also demonstrates that IDA modified onto the surface of Ag NPs. Similar spectral changes were found in Ag NPs modified with bipyridine [27][28][29]. It has been proved that the adsorption of organic compounds on the metal nanoparticles resulted in a red shift in the SPR band, mainly caused by the lessening of the plasma oscillation frequency or a change in the dielectric constant of the microenviroment around the nanoparticles.…”
Section: Resultssupporting
confidence: 66%
“…1b, it is clear that the absorption spectrum of IDA-Ag NPs underwent a little red-shift compared with that of bare Ag NPs, which also demonstrates that IDA modified onto the surface of Ag NPs. Similar spectral changes were found in Ag NPs modified with bipyridine [27][28][29]. It has been proved that the adsorption of organic compounds on the metal nanoparticles resulted in a red shift in the SPR band, mainly caused by the lessening of the plasma oscillation frequency or a change in the dielectric constant of the microenviroment around the nanoparticles.…”
Section: Resultssupporting
confidence: 66%
“…AA [251] BA [251,252] BA [253] MA [54,252] St [254,255] HPA [251] St [256] SMe [251] BP/NPMI [257] S S 93 [216] BA [216] (BA) [216] S S 94* [255] AEP [87] BA [62,216] (BA) [216] TFPA [93] MMBL [258] AcS [259] St [260] St [261] PFS [93] NIPAM [262,263] St/MMBL [258] MMA/BA [62] BP/NPMI [257] BP/NMMI [257] BP/NEMI [257] TFPA-b-tBA [93] PFS-b-tBA [93] …”
Section: *mentioning
confidence: 99%
“…First, we studied the temperatureand pH-responsive behaviors of the polymer@Au-Fe 3 O 4 NPs in the distilled water. However, we knew that heating the polymer-coated Au/Fe 3 O 4 NPs solution (250 mg L -1 ) above the LCST of the copolymer did not result in any change in color or opaque of the polymer@Au/Fe 3 O 4 (Yusa et al 2007;Zhang et al 2013). When the smart polymer-coated Au/Fe 3 O 4 NPs were dispersed in PBS with ionic strength of 10 mM, rather than deionized water, the NPs did display temperature-responsive behavior.…”
Section: Preparation and Characterization Of Polymer@au/ Fe 3 O 4 Npsmentioning
confidence: 99%
“…MC Cormick et al reported that watersoluble polymers prepared by RAFT radical polymerization can stabilize gold NPs by reduction of dithioester end groups to thiol groups in the presence of HAuCl 4 (Lowe et al 2002). Recently, the temperature behaviors of bulk and surface-grafted PNIPAAms were probed, and it was found that surface-bound polymer exhibited more gradual responses over a wide range of temperature (Yusa et al 2007;Shi et al 2014). For example, Hamner et al reported that DNAmediated assembly and encoded nanocarrier drug release could be regulated by thermoresponsive PNIPAAm-b-PMAA-protected AuNP .…”
Section: Introductionmentioning
confidence: 99%